Historical reality and „understanding" the hermeneutical approach - Kęstutis Dubnikas (Lietuvos Istorijos Studijos)
The contemporary philosophy of historiography widely discusses a problem of the cognitive claims. The article, following H. G. Gadamer's hermeneutical philosophy and D. Tracy's theory of "classics," dwells on an elaboration of the methodological distinction between, firstly, historical knowledge and secondly, an understanding of history.